Corticosteroids in the prevention and treatment of infants with bronchopulmonary dysplasia: Part II. Inhaled corticosteroids alone or in combination with surfactants. Issue 4 (12th January 2022) - Szabó, Hajnalka; Baraldi, Eugenio; Colin, Andrew A.
Abstract: This paper is the second in a two‐part State‐of‐the‐Art series that reviews the latest relevant clinical trials investigating the short‐term and long‐term effects of corticosteroids in the prevention and treatment of bronchopulmonary dysplasia (BPD). Inhaled postnatal corticosteroids demonstrate low systemic bioavailability and rapid systemic clearance with high pulmonary deposition and were expected to reduce the incidence of BPD with reduced adverse effects, however, increased rate of mortality in the neonatal period and at the 18–24 months follow‐up was observed. In a milestone study, intratracheal instillation of corticosteroids combined with surfactant decreased the incidence of BPD without increasing the mortality or the long‐term neurodevelopmental adverse outcomes. However, subsequent trials using different types of surfactants, different surfactant to budesonide ratio, different time of the drug administration for infants with different severity of respiratory distress syndrome could not reproduce all the beneficial effects. Future perspectives for the identification of premature infants at high risk of BPD and the prevention or treatment of established BPD are discussed.